Dicam promotes proliferation and maturation of chondrocyte through Indian hedgehog signaling in primary cilia. Issue 7 (July 2018) - Han, S.; Park, H.-R.; Lee, E.-J.; Jang, J.-A.; Han, M.-S.; Kim, G.-W.; Jeong, J.-H.; Choi, J.-Y.; Beier, F.; Jung, Y.-K.
Summary: Objectives: Primary cilium is required for mechano-biological signal transduction in chondrocytes, and its interaction with extracellular matrix is critical for cartilage homeostasis. However, the role of cilia-associated proteins that affect the function of cilia remains to be elucidated. Here, we show that Dicam has a novel function as a modulator of primary cilia-mediated Indian hedgehog (Ihh) signaling in chondrocytes. Methods: Cartilage-specific Dicam transgenic mouse was constructed and the phenotype of growth plates at embryonic day 15.5 and 18.5 was analyzed. Primary chondrocytes and tibiae isolated from embryonic day 15.5 mice were used in vitro study. Results: Dicam was mainly expressed in resting and proliferating chondrocytes of the growth plate and was increased by PTHrP and BMP2 in primary chondrocytes. Cartilage-specific Dicam gain-of-function demonstrated increased length of growth plate in long bones. Dicam enhanced both proliferation and maturation of growth plate chondrocytes in vivo and in vitro, and it was accompanied by enhanced Ihh and PTHrP signaling. Dicam was localized to primary cilia of chondrocytes, and increased the number of primary cilia and their assembly molecule, IFT88/Polaris as well. Dicam successfully rescued the knock-down phenotype of IFT88/Polaris and it was accompanied by increased number of cilia in tibia organ culture. Conclusion: These findings suggest that Dicam positively regulates primary cilia and Ihh signaling resulting in elongation of long bone.